Etiology and risk factors for non-suicidal self-injurious behavior - E. V. Darin; O. G. Zaitseva (Медицинский вестник Юга России, 2023)
The article presents a review of the literature on the subject of non-suicidal self-injurious behavior (NSSI), the study of which attracts the attention of authors, both in the Russian Federation and around the world. Large meta-analyses of NSSP studies, proposed models, probable causes and mechanisms of occurrence, neurobiological factors, social factors, as well as the influence of modern means of communication and social networks are considered. Objective is to study, summarize and present data on the causes and risk factors of non-suicidal self-injurious behavior. Research method — articles in the “MEDLINE/PubMed”, “Scopus” databases in international medical journals were selected and analyzed. Articles were searched by keywords: “Self-Injurious Behavior”, “Non-Suicidal Self Injury”, “Deliberate Self-Harm”, “Self-Harm”, “Risk Factors”. Inclusion criteria: publication date from 2017 to 2022, clinical studies, meta-analyses and systematic reviews, randomized controlled trials, availability of the full text in the public domain or abstract. Exclusion criteria: abstracts; monographs, study guides; publication date until 2017, inconsistency with the research topic. A total of 94 publications were found. The review included 61 publications from 2017 to 2022 that corresponded to the topic and purpose of the study, and also added 19 sources older than 2017 that are significant for disclosing the subject of the study from references in the reference lists of the analyzed sources.